Effects of amount offered and chopping on intake and selection of sorghum stover by Ethiopian sheep and cattle - Osafo, E.L.K.; Owen, E.; Said, A.N.; Gill, M.; Sherington, J. (Cambridge University Press, 1997)
Experiment 1, with rams (17.0 kg initial weight (M), and experiment 2, with steers (203 kg M), involved 2x2 arrangements of treatments to compare the effect of doubling the amount of stover offered (25 or 50 g/kg M daily) and chopping (unchopped or chopped), upon intake, selection and live-weight change. The stover used was a non-bird-resistant, local variety (Dinkamash). The particle length distribution of the chopped stover (produced by a tractor-driven chaff cutter) was: <4.5 mm, 0.148; 4.5 to 8 mm, 9.157; 8 6 12 mm, 0.181; 12 to 20 mm, 0.269; 20 to 33 mm, 0.168; 33 to 54 mm, 0.040; 54 to 90 mm, 0.003; >90 mm, 0.034. The stover was supplemented with minerals and cottonseed cake (sheep, 0.1 kg dry matter (DM) per day; cattle, 0.76 kg DM per day). Experiment 1, over 56 days involved 48 Menz Highland, 18-month-old, rams, with four replicate pens containing three rams. Experiment 2, over 49 days, used 32, individually penned, Friesian X Zebu yealing steers. With rams, doubling the amount offered and chopping increased intake, and the effects were additive (unchopped: 0.98 1.24; chopped: 1.08 1.60 (s.e. 0.71) kg DM per pen per day). With steers, there was an amount X chopping interaction (P<0.05) (unchopped: 3.7 4.7 chopped: 3.6 3.9 (s.e. 0.16) kg DM per day), with chopping reducing intake of stover offered at 50 g/kg M per day. Increased intakes were associated with increased growth rate. In both experiments refused stover contained less leaf-plus-sheath than offered stover but the difference was more pronounced in rams compared with steers indicating the superior selective ability of the rams. In rams offered unchopped stover, the increase in stover intake with increasing amount offered was accounted for by a proportional 1.03 unit increase in consumption of leaf-plus-sheath and a 0.06 unit reduction in intake of stem. Doubling the amount of unchopped stover offered increased intake of both rams and steers by 0.27 unit. Chopping stover was clearly beneficial for rams but not for steers. Doubling the amount of stover offered is a simple excess-feeding strategy to apply. Excess feeding also increases the proportion of stover refused from about 0.2 to 0.5, thus generating an uneaten residue available for other purposes, e.g. mulch or compost.